2021
DOI: 10.3390/curroncol28020139
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Provider Perspectives on Adherence to Adjuvant Endocrine Therapy after Breast Cancer

Abstract: Adherence to adjuvant endocrine therapy (AET) for breast cancer is suboptimal. The purpose of this study was to: (1) explore the experiences and perspectives of healthcare providers (HCPs) in providing care to breast cancer survivors prescribed AET, (2) identify how social and structural factors influence the provision of AET-related care, and (3) ascertain HCP recommendations for optimizing AET adherence and related care. Individual, in-depth interviews were conducted with 14 HCPs using an interpretive descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…A recent study about qualitative health care provider perspectives related to AET acceptance highlighted the pivotal role of a trustful patient-provider relationship. 36 Current results align with published literature, showing that trust in the treating physician is highly relevant for acceptance of AET, outweighing other commonly adopted factors such as age and a less favorable prognosis. 29 In cancer patients with potential life-threatening disease, a trustful patientphysician relationship can be essential for the success of the treatment.…”
Section: Trustsupporting
confidence: 83%
See 2 more Smart Citations
“…A recent study about qualitative health care provider perspectives related to AET acceptance highlighted the pivotal role of a trustful patient-provider relationship. 36 Current results align with published literature, showing that trust in the treating physician is highly relevant for acceptance of AET, outweighing other commonly adopted factors such as age and a less favorable prognosis. 29 In cancer patients with potential life-threatening disease, a trustful patientphysician relationship can be essential for the success of the treatment.…”
Section: Trustsupporting
confidence: 83%
“…However, the difference between both groups is not as pronounced as we had expected, and it is outweighed by beliefs about medicine (especially the concerns regarding AET) and by trust in the treating physician (Table 2). On the assumption that the treating physician supports the AET, especially in patients with higher tumor stage, the physicians' belief might be an important factor in influencing the patients' acceptance 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms and concerns can cause different levels of distress (Mazor et al, 2018;Palmer et al, 2017;Vance et al, 2019) and can impact the quality of life negatively (Lambert et al, 2021). A significant number of patients after primary cancer treatment feel unprepared about how to manage life (Fitch et al, 2020).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…In previous co-development work, patient representatives and healthcare professionals suggested that a website would allow patients to access side-effect management resources when required [71]. Demand for an online resource detailing evidence-based solutions to manage side-effects has also been reported elsewhere [129]. Therefore, a practical strategy to inform women about side-effects and their management was required.…”
Section: Living With Side-effectsmentioning
confidence: 99%